2020
DOI: 10.26464/epp2020007
|View full text |Cite
|
Sign up to set email alerts
|

A new model describing Forbush Decreases at Mars: combining the heliospheric modulation and the atmospheric influence

Abstract: A new model has been developed to quantify Forbush decreases (FD) at Mars, taking into account both the heliospheric and atmospheric modulations of Galactic cosmic rays q The results are in good agreement with FD measurements at both surface and in orbit of Mars q The model can be potentially used to understand the property of Interplanetary Coronal Mass Ejections passing Mars q

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…However, the statistical comparison here suggests that the energy range of the primary GCRs leading to the detected FD may have a larger impact on the FD amplitude, especially when the corresponding energy ranges of the original GCRs are very different at each observer. This highlights the importance of understanding and quantifying the energy-dependent modulation of the GCR particles by solar transients (e.g., Guo et al 2020), enabling the use of FDs to infer the properties of ICMEs.…”
Section: Icme-induced Forbush Decreases On Marsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the statistical comparison here suggests that the energy range of the primary GCRs leading to the detected FD may have a larger impact on the FD amplitude, especially when the corresponding energy ranges of the original GCRs are very different at each observer. This highlights the importance of understanding and quantifying the energy-dependent modulation of the GCR particles by solar transients (e.g., Guo et al 2020), enabling the use of FDs to infer the properties of ICMEs.…”
Section: Icme-induced Forbush Decreases On Marsmentioning
confidence: 99%
“…Since the high energy component of the GCRs is less modulated by solar activity, the surface flux is less sensitive to solar modulation conditions than the primary GCR flux is. Guo et al (2020) have modeled this effect using a GEANT4 based model implemented with the Martian atmospheric and regolith properties (as previously used in Guo et al 2018c) and showed that under a given heliospheric modulation potential, the change of GCR rate on the surface of Mars is smaller than that in deep space.…”
Section: Comparison Of Gcr Variations At Earth Ground In Space and On Marsmentioning
confidence: 99%
“…The amplitude of a FD depends not only on the properties of the heliospheric structure, but also on the energy of the observed GCR particles: lower energy particles are modulated more easily and thus typically show larger FDs (e.g. Lockwood 1971;Lockwood et al 1991;Cane 2000;Guo et al 2020). In the past, the study of FDs was mainly based on data from neutron monitors on the surface of the Earth, but nowadays, GCR measurements suitable for FD studies are also available from many spacecraft in the near-Earth space as well as on other solar system bodies, and these have been routinely used for multi-spacecraft studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that there are other approaches to FD modelling in the FR, such as perpendicular transport by guiding centre drifts (e.g. Krittinatham & Ruffolo 2009;Tortermpun et al 2018), full trajectory integration using CME FR-type models (Petukhova et al 2019), or CME magnetic field reconstructions from in situ measurements (Benella et al 2020), as well as describing FDs via the change in the single GCR spectrum modulation parameter attributed with a CME (Guo et al 2020). However, a recent study by Laitinen & Dalla (2021), in which they performed full-orbit particle simulations, with the interface between the external interplanetary magnetic field and the isolated FR field lines modelled analytically, revealed that the transport around the FR border is fast compared to diffusive radial propagation within the FR.…”
Section: Introductionmentioning
confidence: 99%